2018
DOI: 10.1167/iovs.17-23235
|View full text |Cite
|
Sign up to set email alerts
|

Improved Binocular Outcomes Following Binocular Treatment for Childhood Amblyopia

Abstract: PurposeChildhood amblyopia can be treated with binocular games or movies that rebalance contrast between the eyes, which is thought to reduce depth of interocular suppression so the child can experience binocular vision. While visual acuity gains have been reported following binocular treatment, studies rarely report gains in binocular outcomes (i.e., stereoacuity, suppression) in amblyopic children. Here, we evaluated binocular outcomes in children who had received binocular treatment for childhood amblyopia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 51 publications
2
78
2
Order By: Relevance
“…The most recent research indicates, however, that dichoptic stimulation is capable of reducing suppression depth and extent and improving binocular vision (restoring simultaneous binocular perception). In some cases, this coincides with improved stereoacuity 14,15 . Some studies have proposed a different intervention approach that is focused on the direct stimulation of stereopsis through perceptual learning activities 16,17 .…”
mentioning
confidence: 54%
“…The most recent research indicates, however, that dichoptic stimulation is capable of reducing suppression depth and extent and improving binocular vision (restoring simultaneous binocular perception). In some cases, this coincides with improved stereoacuity 14,15 . Some studies have proposed a different intervention approach that is focused on the direct stimulation of stereopsis through perceptual learning activities 16,17 .…”
mentioning
confidence: 54%
“…We explored BV treatment because it promotes long-lasting recovery of good acuity in both eyes [27] and those findings are similar to promising results of binocular therapies for treating amblyopia in children [65]. Furthermore, there is good physiological recovery with BV [29], [60].…”
Section: Bv Promoted Recovery Of Cp-like Plasticity Phenotype and Idementioning
confidence: 68%
“…Subsequent studies have confirmed this relationship Li et al, 2013;Spiegel et al, 2013). This is clear in adults from the aforementioned studies but not so in children (although see Kelly et al, 2018), from whom it is more difficult to obtain valid measurements of interocular suppression.…”
Section: Discussionmentioning
confidence: 90%
“…It involves re-establishing binocular vision as the first step by using binocularly based training therapy, which relies on a theory that amblyopia and abnormal interocular suppression are causally linked (Baker et al, 2008;Li et al, 2011;Birch, 2013;Ding et al, 2013;Zhou et al, 2013bZhou et al, ,c, 2018. It improves not only binocular vision Hess and Thompson, 2015;Webber et al, 2016;Kelly et al, 2018) but also monocular acuity (Hess et al, 2010bTo et al, 2011;Li et al, 2013Li et al, , 2014Mansouri et al, 2014;Birch et al, 2015). Despite ongoing debate concerning which therapeutic approach is more effective (Holmes et al, 2016;Kelly et al, 2016;Gao et al, 2018;Manh et al, 2018;Pineles et al, 2019), one should bear in mind the possibility that the visual improvements from both approaches might involve the same mechanisms in the brain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation